Pendampingan dan Pelatihan dalam Meningkatkan Kualitas Produksi Kursi Rotan di Kelurahan Kedungkandang Kota Malang - Ratna Nikin Hardati; Siti Muslikah; Warsito Warsito; Mustaufir Mustaufir (Jurnal Surya Masyarakat, 2023)
Currently, many people are pursuing small home industries to improve their welfare and support the resilience of the national economy. One of the home industries that manages wood to make rattan chair crafts is owned by Mr. M. Shodiq in the Kedungkandang sub-district, Kedungkandang sub-district, Malang City. However, several obstacles are still faced by these small industries, including obstacles in increasing the quality and quantity of rattan chair handicraft production due to several factors such as: lack of knowledge about how to process good and varied rattan chair crafts from both the shape and motif aspects, the use of tools which has not been touched by science and technology. The method of community service is socialization about innovation in the development of rattan chair product quality, namely by providing training materials on the use of innovative tools to develop and improve the rattan chair craft industry. The results of this community service include 1) partners have received education and skills in diversifying rattan chair craft products, 2) partners have received appropriate technology-based tools in the form of rattan cutting machines to increase product sales.